Improved Turn-Off Speed and Uniformity of Atomic Threshold Switch Device by AgSe Electrode and Bipolar Pulse Forming - Seungyeol Oh; Seungwoo Lee; Hyunsang Hwang (IEEE Journal of the Electron Devices Society, 2021)
To improve the turn-off speed and uniformity of atomic threshold switching (TS) devices, we propose the use of the AgSe electrode and controlled bipolar pulse forming method. Compared with TS devices with Ag and AgTe electrodes, TS device with the AgSe electrode shows an extremely fast turn-off speed, which can be explained by the limited injection of Ag into the switching layer. By applying positive bias (Icc = 500 nA, 1 ms) followed by negative bias (−0.1 to −0.2 V, $10~μ \text{s}$ ), the TS device exhibits excellent switching uniformity. It can be explained by the formation of atomic-scale filament under the positive bias at low Icc and drift-back of excessive Ag by the negative bias. By designing the shape of the filament and concentration of the residual Ag, the TS device with the AgSe electrode shows promise for selector applications.